Effect of substitution percentage of banana peels flour in chemical composition, rheological characteristics of wheat flour and the viability of yeast during dough time - Shayma Thyab Gddoa Al-Sahlany; Alaa Mohammed Salih Al-musafer (Journal of the Saudi Society of Agricultural Sciences)
The wheat flour was substituted by 1%, 5% and 10% of banana peels flour (BPF) and studied the chemical composition, color of flour, rheological characteristics of flour samples and determination of viable cells of yeast through the dough period. The percentage of the protein and gluten was decreased when the substitution percentage of BPF was increased while carbohydrate percentage was increased. Additionally, the color of flour samples was (6.1, 7.0 and 7.5) Kent-Jones for Iraqi wheat flour was substituted by 1%, 5% and 10% of BPF. Most of the rheological characteristics of the flour samples improved after the substitution process, the 10% of substitution percentage was significantly higher (p ≤ 0.05) compared with the other substitution flour samples and the control (normal flour). The viability cells of Saccharomyces cerevisiae were increased after substituted by 1%, 5% and 10% of BPF through dough time. After 3 h, Log. numbers of Saccharomyces cerevisiae were 7.24 CFU/g of 10% of BPF while the control was 6.37 CFU/g. In conclusion, substituted BPF could be useful for color and rheological characteristics of wheat flour. Moreover, it was increased the yeast numbers during dough time. Keywords: Wheat flour, Rheological properties, Banana peels flour, Saccharomyces cerevisiae